SmartLearnBot Artificial Intelligence as a Pedagogical Innovation in Teacher Education - HARIKRISHNAN, HEMANATHAN (SEAMEO SEAMOLEC, 2025)
This paper presents the development and evaluation of SmartLearnBot, an AI-powered chatbot designed to support digital learning among pre-service teachers enrolled in the Foundation Programme for the Bachelor of Teaching (PPISMP). The chatbot was embedded with content from two compulsory courses, Introduction to Education Studies (GPPP1092) and Fundamentals of Digital Learning (GAPD1032). The aim of this innovation was to provide a responsive, interactive, and accessible learning platform to enhance student engagement and comprehension. The research involved 100 students from two teacher education institutes in Kuala Lumpur. A pre-test and post-test design was employed using structured questionnaires. Results showed a significant increase in students’ understanding, with mean scores rising from 58.6% to 82.4%. Students also reported high satisfaction and a willingness to recommend the tool to peers. The study concludes that SmartLearnBot is a practical and scalable pedagogical innovation aligned with 21st-century learning goals. It is recommended for wider adoption in teacher training programmes to promote flexible, technology-driven instruction.